Need of Women Entrepreneurs in India: A Meta Study (International Journal of Scientific Research and Management (IJSRM), 2017)
About two decades ago if we look we observe that there is a major problem with India’s labour force: the women are missing. Indian women are not only staying out of the workforce, they are doing so in increasing numbers across the board. This is partly the result of the type of businesses that women’s set up in what is already a heavily gendered labour force. For example, a beauty salon or a small tailoring unit owned by a woman can be expected to mostly hire other women. Also, many of these women-owned firms have only a single worker, which also skews the picture. But the trend holds true even in medium-sized firms. This lends credence to the idea that a targeted focus on women’s entrepreneurship might be the tool needed to improve the labour force’s gender balance. This paper attempts to identify the role and need of Women Entrepreneurs in India.